Design of new reversible and selective inhibitors of monoamine oxidase A and a comparison with drugs already approved - A. Reyes-Chaparro; N. S. Flores-Lopez; F. Quintanilla-Guerrero; Dulce Estefanía Nicolás-Álvarez; A. R. Hernandez-Martinez (Bulletin of the National Research Centre, 2023)
Abstract Background Monoamine oxidase (MAO) is an enzyme that has been targeted pharmacologically for the treatment of depression and neurodegenerative diseases such as Parkinson's disease. To avoid side effects, drugs currently in use must selectively target either of the enzyme's two isoforms, A or B. In this study, we designed molecules derived from chalcone as potential reversible and selective inhibitors of isoform A of the MAO enzyme. Results Ten thousand one hundred compounds were designed and screened using molecular docking, considering the pharmacokinetic processes of chemical absorption, distribution, metabolism, and excretion. Density functional theory calculations were performed for the main ligands to evaluate their reactivity. Six drugs qualified as reversible and irreversible inhibitors of both isoform A and isoform B. Among these, molecule 356 was found to be a reversible inhibitor with the best performance in selectively targeting isoform A of the MAO enzyme. The interaction stability of ligand 356 in the isoform A binding site was confirmed by molecular dynamics. One hydrogen bond was found between the ligand and the cofactor, and up to six hydrogen bonds were formed between the ligand and the protein. Conclusions We selected a drug model (molecule 356) for its high affinity to isoform A over isoform B of the MAO enzyme. This proposal should decrease experimental costs in drug testing for neurodegenerative diseases. Therefore, our silico design of a reversible inhibitor of isoform A of enzyme monoamine oxidase can be used in further experimental designs of novel drugs with minimal side effects. Graphical Abstract